IMPLEMENTASI DIGITAL MARKETING UNTUK MENINGKATKAN TRANSAKSI PENJUALAN PADA USAHA BERSAMA MUTIARA - Anggalia Wibasuri; Fitria; MS Hasibuan; Suwandi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The Joint Business Group (KUB) “Mutiara” has a business in processing filter material into several products such as caps, bags, clothes and slings. Determination of selling prices and marketing (marketing) is a problem faced by KUB Mutiara. The determination of the selling price only takes into account wages without reviewing the market price. The marketing model is done by entrusting the goods to the sales center. This community service aims to provide training for determining selling prices and digital marketing. The method used is counseling and training for KUB Mutiara employees. There are 10 craftsmen and 3 admins who are trained to improve product innovation, pricing and digital marketing training. The results achieved after dedication, product innovation grew by 85%, understanding of price determination from not understanding to understanding, increasing sales by 70%